Gene prediction of immune cells association between gut microbiota and colorectal cancer: a Mendelian randomization study - Zhong, Yan; Chen, Guanglei; Chen, Menglu; Cui, Junsong; Tan, Qianren; Xiao, Zhenghua (Frontiers in Immunology, 2025)
BackgroundAn increasing number of studies have revealed that gut microbiota influences the development and progression of Colorectal cancer (CRC). However, whether a causal relationship exists between the two remains unclear, and the role of immune cells in this context is not well understood.ObjectiveTo elucidate the causal relationship between gut microbiota and CRC and to explore the potential mediating role of circulating immune cells.Materials and methodsTo analyze the causal relationship between gut microbiota and CRC, we employed a univariable Mendelian randomization (UVMR) approach. Subsequently, a two-step multivariable Mendelian randomization (MVMR) to assess the potential mediating role of circulating immune cells. Primarily, applied the Inverse-Variance Weighted method to evaluate the causal relationship between exposure and outcome. To ensure the robustness of the results linking gut microbiota and CRC, we validated the findings using Robust Inverse-Variance Weighted, Penalized Inverse-Variance Weighted, and Penalized Robust Inverse-Variance Weighted methods. Additionally, we employed MR-Egger Intercept to mitigate the influence of horizontal pleiotropy. MR-PRESSO was used to detect and correct outliers by excluding anomalous instrumental variables. Finally, we supplemented our analysis with methods such as Bayesian Weighted Mendelian Randomization (BWMR), Maximum-Likelihood, Lasso, Debiased Inverse Variance Weighted, and Contamination Mixture to establish a robust and compelling causal relationship.ResultsAfter accounting for reverse causality, horizontal pleiotropy, and various methodological corrections, Bifidobacterium kashiwanohense, GCA-900066755 sp900066755, Geminocystis, and Saccharofermentanaceae exhibited strong and robust causal effects on CRC. Specifically, CD40 on monocytes (2.82%) and CD45 on CD33+HLA-DR+CD14- cells (12.87%) mediated the causal relationship between Bifidobacterium kashiwanohense and CRC risk. Furthermore, CD45 on CD33-HLA-DR+ (3.94%) mediated the causal relationship between GCA-900066755 sp900066755 and CRC risk. Additionally, terminally differentiated CD4+T cells (11.55%) mediated the causal relationship between Geminocystis and CRC risk. Lastly, CD40 on monocytes (2.35%), central memory CD4+T cells (5.76%), and CD28 on CD28+CD45RA+CD8+T cells (5.00%) mediated the causal relationship between Saccharofermentanaceae and CRC risk.ConclusionOur mediation MR analysis provides genetic evidence suggesting that circulating immune cells may mediate the causal relationship between gut microbiota and CRC. The identified associations and mediation effects offer new insights into potential therapeutic avenues for CRC.